Les métaphores de la santé dans l’économie : le cas de la presse économique espagnole (PHRASIS | Rivista di studi fraseologici e paremiologici, 2019)
For centuries, there has been a well-known analogy with medicine when speaking about economics. According to this mapping, economy may be conceptualized as a living organism, which is composed of different parts and which can suffer from various diseases. The purpose of this work is to find and analyse two types of medical terms in the Spanish economic press: specialized terms, such as names of diseases, and more general terms on health. This study is based on the cognitive perspective of Conceptual Metaphor Theory. To obtain such an analysis, a detection strategy and the compilation of a corpus of economic texts from the Spanish press was carried out (Pamies, Ramos Ruiz, 2017; Ramos Ruiz, 2015), by using an adaptation of the Metaphorical Identification Process proposed by the Pragglejaz group (Crisp et al., 2007). Subsequently, the semi-automatic selection of metaphorical components was completed with the help of the SketchEngine® software.
Keywords: metaphor, phraseology, economic journalism, corpus linguistics